Efek Perekonomian Negara (Inflasi, Upah Minimum, Konsumsi, Kurs Tukar, Investasi, dan Pengeluaran Pemerintah) Terhadap Pertumbuhan Manufaktur di Indonesia: Pendekatan Error Correction Model (ECM) - Galih Priyo Anggoro; Indah Susilowati; Abdul Rouf; Purbayu Budi Santosa; Darwanto Darwanto; Deden Dinar Iskandar; Abdul Karim; Wahyu Widodo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the effects of inflation, minimum wage, household consumption, exchange rate, investment, and government expenditure on the growth of Indonesia’s manufacturing industry during the 1990–2024 period. The study employs a quantitative approach using annual time-series data consisting of 35 observations and is analyzed using the two-step Engle–Granger Error Correction Model (ECM). The Augmented Dickey–Fuller and Phillips–Perron tests indicate that all variables are integrated of order I(1), while the cointegration test confirms the existence of a long-run relationship. The estimation results show that investment has a significant positive effect on manufacturing growth, whereas government expenditure has a significant negative effect, indicating a crowding-out effect. The Error Correction Term coefficient of -1.046 (p < 0.01) confirms the adjustment mechanism toward long-run equilibrium. In the short run, changes in investment and government expenditure are the main determinants of manufacturing growth. These findings highlight the importance of strengthening the investment climate and allocating government expenditure more productively to support the growth of the manufacturing sector.